Change communication and the use of anonymous social media at work: Implications for employee engagement. (5th June 2019) - Kim, Heewon; Scott, Craig
Abstract : Purpose: The purpose of this paper is to investigate how employees use anonymous social media to cope with organizational change, which may affect various engagement outcomes. Specifically, this study focuses on change communication from management (i.e. top–down communication) and workplace freedom of speech (i.e. bottom–up communication) as potential antecedents of anonymous communication. In turn, commitment, turnover intention and job satisfaction are examined as engagement outcomes. Design/methodology/approach: An online survey was conducted at Microsoft through Blind, a mobile platform for anonymous communication at work. A series of regression models were used to test hypotheses. Findings: Results demonstrate that: the quality of change communication was related to anonymous social media use for information and support seeking; workplace freedom of speech was related to anonymous social media use for expressing ideas; perceived usefulness and trustworthiness of anonymous social media positively affected the usage of them; and the quality of change communication and workplace freedom of speech were linked to affective commitment and job satisfaction. Originality/value: Despite the growing popularity of anonymous social media at work, their use and influences have received scarce empirical attention. This study advances the authors' knowledge of the antecedents, characteristics and outcomes of anonymous social media use in a work environment characterized by frequent organizational changes. The findings also highlight the significance of communication qualities and freedom of speech at work.